Severe adenomyosis with unexpectedly high CA-125: report of a rare case - Abdelazim, Ibrahim; AbuFaza, Mohannad; Hamed, Mohamed E.S.; Bekmukhambetov, Yerbol; Zhurabekova, Gulmira; Shikanova, Svetlana (Menopause Review/Przegląd Menopauzalny, 2020)
A 46-year-old woman presented to the emergency department with abdominal pain and abnormal uterine bleeding over the last year. She had a history of failed cyclic progesterone with tranexamic acid over the last 3 months to control her bleeding attacks. She had a tender pelvi-abdominal mass of 28 weeks’ gestation size. Therapeutic curettage was performed, followed by correction of her iron deficiency anemia with intravenous iron. The trans-abdominal ultrasound of the pelvi-abdominal mass showed asymmetrical myometrial thickening, predominantly its anterior wall, with myometrial hyperechoic regions surrounded by hypoechoic areas suggestive of adenomyosis uterus for magnetic resonance imaging (MRI) evaluation. The MRI evaluation confirmed the diagnosis of adenomyosis uterus and showed diffuse asymmetrical uterine adenomyosis, predominantly its anterior myometrial wall, with an ill-defined endo-myometrial junction. Total abdominal hysterectomy with bilateral salpingectomy and bilateral ovarian conservation was performed after departmental approval and the patient’s consent. The routine pre-operative investigations were completely normal except the cancer antigen (CA-125) which was unexpectedly high (1658 and 1046 IU/ml repeated twice two days apart). The histological examination of the surgical removed uterus confirmed the diagnosis of adenomyosis uterus and the pre-operative high CA-125 decreased to 22 IU/ml (normal range 0-35 IU/ml) one week after surgery. Conclusions: Unexpectedly high CA-125 over 1000 IU/ml can be seen in benign gynecologic conditions such as severe adenomyosis. The high CA-125 level is positively correlated to the uterine size in severe adenomyosis.